Validity of Marital Conflict Resolution Scale Using Reflective Measurement Model of PLS-SEM - Sitti Murdiana (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2020)
AbstractThis research describes the validity of marital conflict resolution scale that formulated from Gottman theory about marital conflict resolution. Marital conflict resolution scale presented to 255 married women in Makassar city. Consisting of 26 items, marital conflict resolution scale there are two dimensions consisting of constructive resolution and destructive resolution. Constructive resolution consist 11 items and destructive resolution consist 15 items has had five choices of the answer. The answer ranging from strongly agree (1 score) to strongly disagree (5 score) for favorable item, and unfavorable items get the opposite score. Validity of marital conflict resolution scale is tested using the reflective measurement model of PLS-SEM. The results of the outer model and the structure or inner model have shown the original sample estimate ≥ 0.50, this means that each indicators can represent both dimensions.AbstrakPenelitian ini menguraikan mengenai validitas skala penyelesaian konflik perkawinan yang dirumuskan dari teori Gottman tentang penyelesaian konflik perkawinan. Skala penyelesaian konflik perkawinan diberikan kepada 255 responden wanita menikah di kota Makassar. Terdiri dari 26 item, skala penyelesaian konflik perkawinan memiliki dua dimensi yang terdiri dari penyelesaian konstruktif dan penyelesaian destruktif. Penyelesaian konstruktif terdiri dari 11 item dan penyelesaian destruktif terdiri dari 15 item memiliki lima pilihan jawaban. Jawaban mulai dari sangat setuju (1 skor) hingga sangat tidak setuju (5 skor) untuk item yang menguntungkan, dan item yang tidak menguntungkan mendapatkan skor yang berlawanan. Validitas skala penyelesaian konflik pernikahan diuji menggunakan model pengukuran reflektif PLS-SEM. Hasil outer model dan struktur atau inner model menunjukkan original sample estimate ≥ 0,50, ini berarti bahwa masing-masing indikator dapat mewakili kedua dimensi.